Evaluating categories of resistance in soybean genotypes from the United States and Brazil to Aphis glycines (Hemiptera: Aphididae) - Baldin, Edson L. L. [UNESP] (2016)
Aphis glycines Matsumura (Hemiptera: Aphididae), the soybean aphid, has become an important pest of soybeans, leading to significant yield losses in the United States. Host plant resistance is a viable alternative for managing A. glycines. The objectives of this study were to identify and categorize sources of resistance in soybean to A. glycines on genotypes from the United States and Brazil. An antixenosis assay was initially conducted with 8 genotypes to evaluate attractiveness to A. glycines. The selected soybean genotypes were further evaluated in a colonization assay to investigate the resistance of the genotypes at V1 (fully developed leaves at unifoliate node, 1st trifoliate leaf unrolled) and V3 (fully developed leaf at 2nd trifoliate node, 3rd trifoliate leaf unrolled) stages. An antibiosis assay was also conducted, in which multiple biological parameters of A. glycines were recorded. In the antixenosis assay, PI 200538, IAC 24, and IAC 17 genotypes were least attractive to adults of A. glycines, indicating moderate levels of antixenosis. The colonization assay showed that genotypes infested at the V3 stage had greater resistance when compared with the respective plants infested at the V1 stage. In addition, high levels of antibiosis to A. glycines were found in UX 2569-159, PI 200538, and PI 243540 genotypes. The identification of soybeans with resistance to A. glycines is of importance for the integrated pest management of this insect pest in the United States. Moreover, this research represents the first report on potential sources of resistance to A. glycines in soybeans from Brazil.